POTENSI LARVA Hermetia illucens SEBAGAI PEREDUKSI LIMBAH INDUSTRI PENGOLAHAN HASIL PERIKANAN - Arif Rahman Hakim; Agus Prasetya; Himawan T.B.M Petrus (Universitas Gadjah Mada, 2017)
Organic waste from processing fishery products can be a serious problem if not handled properly, as the number increases every year. Though the content of nutrients in the waste is still high, especially protein content. The bioconversion process of organic matter from the waste is expected to be able to overcome the problems of industrial waste and increase its added value. Bioconversion using insect larvae Hermetia illucens has many advantages than other conversion processes. The purpose of this study was to determine the ability of larvae in reducing the waste fishery industry. Waste used in this study was head of the tuna, with feeding rates of 60, 80 and 100 mg/larva/day. 200 larvae were used in each treatment and 3 replications. Observation time and culturing of larvae was 19 days then calculated substrate reduction, waste reduction index (WRI), the weight of larvae and protein and lipids content. The result of observations showed that feeding rate 60 mg/larva/day give optimum on parameters. The substrate reduction was 77.09%, WRI 4.06 (% / day), the weight of larva was 72.59 mg. Protein content 25.38 % (wb) and lipids 6.85 % (wb). According to that result, it could be to concluded that larvae have potential as an agent of reducing of waste fishery products.